The effects of peer to peer lending on online credit loan in Palembang / Kardinal Kardinal and Ratna Juwita - -, Kardinal Kardinal; -, Ratna Juwita (UiTM Cawangan Johor, 2019)
This Research investigated the effects of peer to peer lending on online credit loan. The result showed process, loans of credit, requirement and used to loan had positive and significant effect on online credit loan, the increased process, loans of credit, requirement and used to loan would increased online credit loan.